Ecological Niche and Conservation Strategies of Spondias mombin L. in the Context of Climate and Global Change in Benin (West Africa) - GANGLO, COSSI JEAN; Togni, Yolande (My University, 2024)
Spondias mombin L. of the Anacardiaceae family, is sought for their nutritional and medicinal value. In order to have relevant scientific information on how the spatial distribution of Spondias mombin L. could be affected by climate change, its ecological niche was modelled. Occurrences of Spondias mombin L were downloaded from the Global Biodiversity Information Facility (GBIF) website and supplemented with those collected in the field. The present climatic environmental data were downloaded from Worldclim 2.1 and, the projection environmental layers were downloaded from the Africlim website. Soil and population data were respectively downloaded from African Soil Profiles database and SEDAC websites at 2.5 minutes resolution. In total, 1474 occurrence data were used for S. mombin modelling in Maxent. Five variables were selected to predict the ecological niche of the species. Soil, population and bio6 contribute mainly to the prediction of the distribution model of this species. The results show also an extension of the favorable areas of S. mombin. In addition, protected areas in favorable areas are and will remain very beneficial to their conservation. Strategies for sustainable management of S. mombin must encourage reforestation initiatives with this species, raise awareness among local communities close to populations
Keywords: Spondias mombin; Climate Change; Maxent; Favorable Areas; Protected Areas; Benin